Associated Risk Factors in Group B Streptococcus Infection During Pregnancy - HUANG Yan, WANG Mingying, FENG Junyan, ZHANG Jie (Zhongguo quanke yixue, 2022)
BackgroundGroup B streptococcus (GBS) infection can give rise to intrauterine infection during pregnancy and postpartum endometritis, and increase the risk of premature birth or stillbirth. So it is essential to improve the detection rate of GBS and to identify risk factors of GBS infection.ObjectiveTo explore the risk factors of GBS infection during pregnancy.MethodsParticipants were pregnant women in late pregnancy (n=11 248) who were selected from Department of Obstetrics and Gynecology, Peking University International Hospital from January 2017 to August 2021. All of them underwent screening for GBS infection, 4 479 of them used vaginal swab test (single-swab culture group) , 1 239 used vaginal and rectal swabs tests (double-swab culture group) , and other 5 530 used PCR test of vaginal and rectal swabs (double-swab & PCR group) , and GBS detection rates in the groups were compared. Then, from the double-swab & PCR group, 305 cases who were detected with GBS infection and 2 650 without were selected and compared in terms of information possibly related to GBS infection collected from the medical records, by which potential intrapartum risk factors for GBS infection were identified exploratively. Furthermore, 294 of the above-mentioned 305 cases who also underwent vaginal microbiome test were selected, and compared with a random sample of 367 of the above-mentioned 2 650 cases who also underwent vaginal microbiome test, to analyze the association of vaginal microbiota status with GBS infection.ResultsThe GBS detection rates in single-swab culture group, double-swab culture group, and double-swab & PCR group were 5.94% (266/4 479) , 8.07 (100/1 239) , and 10.31% (570/5 530) , respectively. The GBS detection rate was lower in single-swab culture group than that of other two groups (P<0.017) . And double-swab & PCR group had a higher GBS detection rate than did double-swab culture group (P<0.017) . Multiple Logistic regression analysis showed that grade Ⅲ or Ⅳ vaginal cleanliness was closely associated with the prevalence of GBS infection in pregnancy〔OR=3.005, 95%CI (1.220, 7.403) , P=0.017〕.ConclusionPCR test of both vaginal and rectal swabs could increase the GBS detection rate. Vaginitis is a major high-risk factor associated with GBS infection during pregnancy, which needs to be addressed in the process of diagnosis and treatment.